The Relationship of Long Work When Using Laptop With Carpal Tunnel Syndrome (CTS) in College Students - Anna Maria Mesia; Luh Putu Ruliati; Agus Setyobudi (Journal of Health and Behavioral Science, 2022)
Carpal tunnel syndrome is one musculoskeletal disorder that often occurs in work that uses the wrist repeatedly in a position that is not ergonomic for a long time. Use of laptops by students sometimes does not pay attention to ergonomics when typing by using a laptop properly and correctly, so it becomes one of the risk factors for CTS. This study aimed to determine the prevalence of a long-standing relationship between p CTS events, repetitive movements, and wrist posture with CTS incidence in students of the Class of 2017 IKM UNDANA Study Program. This research is a type of quantitative research cross-sectional study design. This study showed no relationship between long-standing with using the laptop, repetitive movements, and wrist posture with complaints of carpal tunnel syndrome in students of the class of 2017 IKM UNDANA study program. This research shows that there needs to be good time management when typing using a laptop, especially for students.